Combining Abilities of Carcass Traits among Pure and Crossbred Meat Type Chickens - Adebambo, A.O.; Adeleke, M.A.; Whetto, M.; Peters, S.O.; Ikeobi, C.O.N.; Ozoje, M.O.; Oduguwa, O.O.; Adebambo , Olufunmilayo A. (International Journal of Poultry Science, 2010)
Two hundred and ninety five cocks and two hundred and ninety nine hens were selected from a diallel combination of four breeds of chickens; [Anak Titan (A), Alpha (B), Giriraja (G) and Normal indigenous (N) chickens] at 12 weeks of age in a broiler improvement program for carcass analysis. The following data were collected in percentages: economically important traits = Live weight (g), Plucked weight, Eviscerated weight, Carcass yield, Abdominal fat percentage, Breast yield, Thigh yield, Drumstick yield; survival organs = Wing yield, Internal organ, Empty gizzard yield, Heart yield, Lung yield, Kidney yield, Liver yield. Analyses of variance of carcass traits show that sire and dam genotype significantly (p